Saving Calvinism: expanding the reformed tradition - Crisp, Oliver (IVP Academic, 2016)
On Calvinism -- God's eternal purpose -- Free will and salvation -- Calvinism and universalism -- Calvinism and the cross -- Calvinism and the extent of the atonement